KARAKTERISTIK MINYAK HASIL PIROLISIS BATCH SAMPAH PLASTIK POLYETHYLENE DAN POLYSTYRENE PADA BERBAGAI SUHU - , Indah Noor Dwi KD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Efforts are being carried out in order to utilize polyethylene (PE) and polystyrene (PS) plastic waste by converting them into fuel or oil. One technology that can be used is pyrolysis. This study aims to (1) determine the quantity and the characteristics of oil from the results of pyrolysis polyethylene (PE) and polystyrene (PS) plastic waste at various temperatures which include characteristics of physics (specific gravity, heating value, flash point, pour point, and kinematic viscosity) and chemical characteristics (composition compounds in oil), (2) determine the optimal conditions of process pyrolysis related to the quality and quantity of oil by pyrolysis, and (3) determine the potential treatment of PE and PS plastic waste by pyrolysis method. The materials used in this study were the type of polyethylene (plastic bags) and polystyrene/styrofoam (for fruits or vegetables) plastic waste. The selected temperature variations are T = 400oC, 450oC, and 500oC. Pyrolysis oil was weighed and measured its volume to obtain v/wo and yield. The results showed that the quantity of pyrolysis oil from polyethylene (PE) plastic waste at temperatures of 400, 450, and 500oC based on v/wo (ml/g) respectively were 0.3429 ml/g